2015
DOI: 10.1039/c5ra15793e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spermine on the morphology, digestive enzyme activities, and antioxidant status of jejunum in suckling rats

Abstract: Spermine is a ubiquitous cellular component that plays vital roles in the maintenance of nucleic acids, regulation of kinase activities, protein synthesis, control of ion channel activities and renewal of the gut epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 45 publications
6
43
1
Order By: Relevance
“…COS ingestion significantly increased the representative enzymatic antioxidant activities (SOD and CAT) in the present study, suggesting that COS ingestion can partly enhance the function of antioxidant defence systems by improving enzymatic antioxidant activity25. A recent study reported that GSH and T-AOC are regarded as participants in non-enzymatic antioxidant defence systems26. Here, we found that dietary COS supplementation significantly elevated amniotic fluid T-AOC activity.…”
Section: Discussionsupporting
confidence: 70%
“…COS ingestion significantly increased the representative enzymatic antioxidant activities (SOD and CAT) in the present study, suggesting that COS ingestion can partly enhance the function of antioxidant defence systems by improving enzymatic antioxidant activity25. A recent study reported that GSH and T-AOC are regarded as participants in non-enzymatic antioxidant defence systems26. Here, we found that dietary COS supplementation significantly elevated amniotic fluid T-AOC activity.…”
Section: Discussionsupporting
confidence: 70%
“…In juvenile Jian carp, trypsin and lipase activities in intestine significantly increased with higher levels of dietary arginine (Chen et al, ). Arginine metabolites, such as NO and polyamines, might involve in the beneficial effects on digestive and absorptive enzyme activities (Cao et al, ; DiMagno, Hao, Tsunoda, Williams, & Owyang, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that exorbitant dose of spermine have numerous side effects, such as reduced microbe, tumors development, growth decrease and even cell death (Cipolla et al, 2010). On the other hand, spermine at the appropriate dose can exert beneficial effects, including intestinal growth promotion and the antioxidant capacity improvement (Cao et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…Spermine-induced effects in guts can be associated with morphological and physiological alterations, such as weight and length enhancement, villus increase, crypt depth decrease, enzymes activities enhancement/decrease and macromolecular metabolism improvement (Cao et al, 2015;Liu et al, 2015;Fang et al, 2016). Moreover, spermine was reported to be a free radical scavenger, so it can protect mammalian cells from reactive oxygen species (ROS) in vitro (Ha et al, 1998) and improve the antioxidant capacity of the suckling animals serum or duodenum (Cao et al, 2015;Fang et al, 2016). However, there is no information about the relationship between spermine and the antioxidant capacity of weaned animal liver and spleen in vivo.…”
Section: Introductionmentioning
confidence: 99%